Smart Technology of CO2 Monitoring as Prevention of Acute Respiratory Infection Disease Using Artificial Intelligence Algorithm - Muhammad Shodiq; Agus Priyono; M. Cahyo Kriswantoro3 (Universitas Muhammadiyah Riau, 2024)
Air pollution is a serious environmental problem that can affect human health because it contains toxic gases, one of which is carbon dioxide (CO2). This toxic gas can cause Acute Respiratory Infection (ARI). ARI is an acute infection of the respiratory tract that can cause death. One effort to prevent ARI is to monitor CO2 gas as a trigger for ARI. This study develops intelligent technology for monitoring CO2 concentration using a rule-based artificial intelligence algorithm by utilizing Internet of Things technology integrated with telegrams to provide warnings. Rule-based systems are part of artificial intelligence that have advantages and limitations that need to be considered before deciding whether it is the right technique to use in solving existing problems. This study uses daily data taken by CO2 gas sensors from 07.00 - 16.15 WIB with a data collection range of 15 minutes with a total of 38 data samples taken. The results of the study show that this rule-based algorithm is able to classify CO2 concentrations according to the rules that have been made. In addition, from the data taken, 42% are in the safe category, 50% are in the alert category and 8% are in the danger category, each of which has an effect on health. The system that was built can also send danger notifications via telegram